Seed Germination and Seed Storage Behaviour of Eremostachys superba: an Endangered Medicinal and Ornamental Herb of India - Panwar, G. S.; Srivastava, S. K. (Indian Forester, 2015)
The present study describes seed viability, germination and storage behaviour studies of Eremostachys superba seeds under controlled condition. Eremostachys superba is an endangered medicinal and ornamental herb of North-West Himalaya. Fresh seeds exhibited 98% seed viability and a gradual decrease in seeds stored for different durations at room temperature (RT) and 0-4°C in refrigerator. Maximum germination percentage was observed in seeds stored at 0-4°C for 6-months (35.15%) as compared to the freshly collected seeds (5.7%). Seed germination percentage was enhanced by presoaking the seeds in different concentrations of gibberellic acid. Presoaking of seeds in 400ppm of GA3 was found most effective and 79.32% and 29.43% germination was reported in the seeds soaked in 400ppm GA3 and stored for 6-months at 0-4°C while 29% germination was seen in freshly collected seeds stored at the same temperature and duration. Seeds stored for 6 months at 0-4°C, after presoaking for 24 hours in 400ppm GA3 and sowing in the month of August were found to be most conducive for propagation.